A prevalence study of ocular manifestations in HIV positive patients on highly active anti-retroviral therapy - Hothi, Hemal S.; Gohil, Neepa R.; Parekh, Nilesh V.; Patel, Sagar S. (International Journal Of Community Medicine And Public Health, 2019)
Background: Among 40 million cases worldwide, 50-75% of patients have at least one ocular manifestation in their lifetime. Many of ocular infections are treatable with therapeutic agents. Ocular manifestations invariably reflect systemic disease and can be the initial manifestations of HIV in many cases. Understanding of ocular sequel of HIV infection can lead to the early diagnosis and effective treatment. This study emphasizes on the need of developing a specific ophthalmic examination for the management of ocular manifestations in HIV infected patients. Methods: Cross sectional and observational study of 100 HIV positive participants on HAART were done irrespective of presence or absence of ocular symptoms. Participants were examined for complete ocular examination. Prevalence find out using chi-square test, find p values and ensuring statistical significance. Results: In our study, prevalence of ocular manifestation in HIV positive patients receiving HAART was 39%. Out of them, 20% adnexal involvement, 28% anterior segment involvement, 33% posterior segment involvement, 11% neuro-ophthalmic abnormality, 4% orbital involvement were present. 76% patients belonged to WHO clinical stage 2 and 3. 51% had CD4+ T cell counts <200 cells/µl. Conclusions: Posterior segment followed by anterior segment are the most commonly encountered ocular manifestations of HIV infection. Low CD4 count is good predictor for ocular manifestations in HIV positive patients. Higher WHO stage is also directly related with the severity of the ocular symptoms. Routine baseline ophthalmic screening to all HIV positive patients are necessary to prevent ocular morbidity.